2012
DOI: 10.1128/jcm.06625-11
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Analysis of Ureaplasma urealyticum and Ureaplasma parvum Compared with Host Immune Response in Preterm Neonates at Risk of Developing Bronchopulmonary Dysplasia

Abstract: Multiplex, real-time PCR for the identification of Ureaplasma urealyticum and Ureaplasma parvum was performed on nucleic acids extracted from sequential endotracheal aspirates obtained from preterm neonates born at <29 weeks of gestation and ventilated for more than 48 h admitted to two level 3 neonatal intensive care units. Specimens were obtained shortly after birth and sequentially up until extubation. One hundred fifty-two specimens (93.8%) contained material suitable for analysis. Ureaplasma spp. were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Little is known about differences in virulence among certain serovars (Abele-Horn et al, 1997 ; Sung et al, 2011 ; Paralanov et al, 2012 ; Sweeney et al, 2017 ). While some studies reported on a predominance of U. parvum in clinical isolates (Sung et al, 2011 ; Payne et al, 2012 ; Friedland et al, 2015 ), other studies failed to designate serovars more often associated with invasive disease and adverse pregnancy outcomes than others (Xiao et al, 2011 ; Paralanov et al, 2012 ). In the present study, we did not observe significant differences between U. urealyticum serovar 8 and U. parvum serovar 3 concerning the pro-inflammatory and immunomodulatory capacity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Little is known about differences in virulence among certain serovars (Abele-Horn et al, 1997 ; Sung et al, 2011 ; Paralanov et al, 2012 ; Sweeney et al, 2017 ). While some studies reported on a predominance of U. parvum in clinical isolates (Sung et al, 2011 ; Payne et al, 2012 ; Friedland et al, 2015 ), other studies failed to designate serovars more often associated with invasive disease and adverse pregnancy outcomes than others (Xiao et al, 2011 ; Paralanov et al, 2012 ). In the present study, we did not observe significant differences between U. urealyticum serovar 8 and U. parvum serovar 3 concerning the pro-inflammatory and immunomodulatory capacity.…”
Section: Discussionmentioning
confidence: 99%
“…have been reported to be the most common organisms isolated from the amniotic fluid, cord blood, respiratory tract and the cerebrospinal fluid of preterm infants who develop bronchopulmonary dysplasia (BPD) (Goldenberg et al, 2008 ; Sung et al, 2011 ; Lowe et al, 2014 ; Viscardi, 2014 ). However, while respiratory tract colonization has been associated with BPD by several investigations (Schelonka et al, 2005 ; Viscardi and Hasday, 2009 ; Lowe et al, 2014 ), multivariable analysis did not confirm this relationship in other studies (Van Waarde et al, 1997 ; Payne et al, 2010 , 2012 ; Kacerovsky et al, 2014 ).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The findings reported herein raise the intriguing hypothetical possibility that Ureaplasma species may be associated with unexplained hyperammonemia in patients other than lung transplant patients. A study evaluating host immune response in preterm neonates at risk of developing bronchopulmonary dysplasia showed that Ureaplasma DNA could be detected at low levels and decreased over time [ 17 ], raising the hypothetical possibility that Ureaplasma species could explain some cases of transient hyperammonemia of the preterm infant [ 18 ]. Unexplained hyperammonemia also occurs in intensive care unit patients, raising the hypothetical possibility that it too could relate to Ureaplasma species.…”
Section: Discussionmentioning
confidence: 99%